The Structures and Binding Modes of Small-Molecule Inhibitors of Pseudomonas aeruginosa Elastase LasB - Virgyl Camberlein; Gwenaëlle Jézéquel; Jörg Haupenthal; Anna K. H. Hirsch (MDPI AG, 2022)
Elastase B (LasB) is a zinc metalloprotease and a crucial virulence factor of Pseudomonas aeruginosa. As the need for new strategies to fight antimicrobial resistance (AMR) constantly rises, this protein has become a key target in the development of novel antivirulence agents. The extensive knowledge of the structure of its active site, containing two subpockets and a zinc atom, led to various structure-based medicinal chemistry programs and the optimization of several chemical classes of inhibitors. This review provides a brief reminder of the structure of the active site and a summary of the disclosed P. aeruginosa LasB inhibitors. We specifically focused on the analysis of their binding modes with a detailed representation of them, hence giving an overview of the strategies aiming at targeting LasB by small molecules.